BOOKS RECEIVED. (Science Fiction Studies, 2014)
A list of books received for the November 2014 issue of "Science Fiction Studies" is presented including "Science Fiction, Alien Encounters, and the Ethics of Posthumanism: Beyond the Golden Rule," by Elana Gomel, "Call and Response," by Paul Kincaid, and "Science Fiction: A Guide for the Perplexed," by Sherryl Vint.